DESIGN PHYSICS PROPS BASED ON ARDUINO NANO SENSORS ON IRREGULARLY CHANGING STRAIGHT MOTION MATERIALS (GLBB) - Rio Sebastian; Handoyo Saputro; Puji Hariati Winingsih (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2021)
This study aims to design, test the feasibility and measure the response of students of physics teaching aids based on Arduino Nano sensors on Regularly Changing Straight Motion (GLBB) material. This study uses the method of research and development (Research and Development). The subjects of this study consisted of four validators and 16 students. Data analysis was carried out by descriptive analysis. The results of the feasibility test of the props product obtained a mean score of 3.54 with very good criteria. The results of the students' responses to the teaching aids obtained a mean score of 2.91 with agreed criteria.